Coal and the Industrial Revolution, 1700-1869 - Gregory Clark; David S. Jacks (University of California, Department of Economics, 2006)
How important was coal to the Industrial Revolution? Despite the huge growth of output, and the grip of coal and steam on the popular image of the Industrial Revolution, recent cliometric accounts have assumed coal mining mattered little to the Industrial Revolution. In contrast both E. A. Wrigley and Kenneth Pomeranz have made coal central to the story. This paper constructs new series on coal rents, the price of coal at pithead and at market, and the price of firewood, and uses them to examine this issue. We conclude coal output expanded in the Industrial Revolution mainly as a result of increased demand rather than technological innovations in mining. But that expansion could have occurred at any time before 1760. Further our coal rents series suggests that English possession of coal reserves made a negligible contribution to Industrial Revolution incomes.
Keywords: 330; Kohlenbergbau; Industrialisierung; Geschichte; Großbritannien